Association between position-specific impact and movement characteristics of professional rugby union players during game play - Peek, R. J.; Carey, D. L.; Middleton, K. J.; Gastin, P. B.; Clarke, A. C. (The Journal of Strength and Conditioning Research, 2023)
The aim of this study was to understand the association between impact and movement characteristics during whole game and peak 1- to 10-minute rolling windows in professional rugby union. Maximal impact (impacts/min) and corresponding running (m/min) characteristics as well as maximal running (m/min) and corresponding impact (impacts/min) characteristics were obtained for 160 athletes from 4 teams across the 2018 and 2019 Super Rugby seasons. A linear mixed-effects model reported a positive association between whole-game running and impacts, where greater impact characteristics corresponded with greater running characteristics. The average 1-minute peak running characteristics (150-160 m/min) typically occurred when no impacts occurred. The average 1-minute peak impact characteristics (4-6 impacts/min) corresponded with an average relative distance of 90-100 m/min. Worst case scenario observed impact characteristics as large as 15 impacts/min with a corresponding relative distance of 140 m/min. When training for peak period characteristics, running may be completed in isolation; however, peak impacts often occur in conjunction with moderate to high running movements. Given running and impact characteristics can appear concurrently within game play, this highlights the need to train them accordingly. As such, when prescribing training drills to replicate the peak characteristics in rugby union, consideration should be taken for both running and impact characteristics.